2013
DOI: 10.2147/jpr.s52195
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of DigiGait™ and TreadScan™ imaging systems: assessment of pain using gait analysis in murine monoarthritis

Abstract: PurposeCarrageenan-induced arthritis is a painful acute arthritis model that is simple to induce, with peak pain and inflammation occurring at about 3 hours. This arthritis model can be evaluated using semiquantitative evoked or non-evoked pain scoring systems. These measures are subjective and are often time- and labor-intensive. It would be beneficial to utilize quantitative, nonsubjective evaluations of pain with rapid assessment tools. We sought to compare the DigiGait™ and TreadScan™ systems and to valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…In a rat model of carrageenan-induced arthritis, the 5 parameters relating to the injured foot had opposite results when tested on the DigiGait versus TreadScan 32 . The authors suggest differences in chamber size, color, lighting, and treadmill belts may explain the variation; however, neither system provided acceptable reproducibility 32 . This highlights the importance of consistency and is a reminder that small methodological factors can play a large role in rodent gait analysis.…”
Section: Spatiotemporal Characterizationmentioning
confidence: 95%
“…In a rat model of carrageenan-induced arthritis, the 5 parameters relating to the injured foot had opposite results when tested on the DigiGait versus TreadScan 32 . The authors suggest differences in chamber size, color, lighting, and treadmill belts may explain the variation; however, neither system provided acceptable reproducibility 32 . This highlights the importance of consistency and is a reminder that small methodological factors can play a large role in rodent gait analysis.…”
Section: Spatiotemporal Characterizationmentioning
confidence: 95%
“…As described previously [76, 77], gait parameters were measured using the Tread-Scan Gait Analysis System (Clever Sys, Reston, VA). Mice were started at 8 cm/s and treadmill speed was adjusted until each mouse maintained a consistent walking speed.…”
Section: Methodsmentioning
confidence: 99%
“…Prior work has shown that significant methodological and material differences in gait analysis systems can yield inconsistent results when applied to identical rodent videos 10 . To be clear, methodological advantages in our approach were not examined relative to commercial systems, nor do we claim any advantage over these packages.…”
Section: Discussionmentioning
confidence: 99%
“…AGATHA, however, does provide an open-source platform which has been validated to manual digitization, and through which these methodological sources of variability can be examined. Unfortunately, little literature is devoted to assessing these methodological sources of error in rodent gait analysis platforms 10,23,32,46 . The limited number of system comparison studies is partly due to lack of gait system access, proprietary software protection, and testing bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation